A microfluidic system for precisely reproducing physiological blood pressure and wall shear stress to endothelial cells. Issue 19 (1st September 2021) - Na, Jing-Tong; Hu, Si-Yu; Xue, Chun-Dong; Wang, Yan-Xia; Chen, Ke-Jie; Li, Yong-Jiang; Wang, Yu; Qin, Kai-Rong
Abstract : This paper reports a novel microfluidic system containing a microfluidic chip with a feedback control system to precisely and stably reproduce the physiologically relevant BP and WSS signals in the human common carotid artery. Abstract : To reproduce hemodynamic stress microenvironments of endothelial cells in vitro is of vital significance, by which one could exploit the quantitative impact of hemodynamic stresses on endothelial function and seek innovative approaches to prevent circulatory system diseases. Although microfluidic technology has been regarded as an effective method to create physiological microenvironments, a microfluidic system to precisely reproduce physiological arterial hemodynamic stress microenvironments has not been reported yet. In this paper, a novel microfluidic chip consisting of a cell culture chamber with on-chip afterload components designed by the principle of input impedance to mimic the global hemodynamic behaviors is proposed. An external feedback control system is developed to accurately generate the input pressure waveform. A lumped parameter hemodynamic model (LPHM) is built to represent the input impedance to mimic the on-chip global hemodynamic behaviors. Sensitivity analysis of the model parameters is also elaborated. The performance of reproducing physiological blood pressure and wall shear stress is validated by both numerical characterization and flow experiment. Investigation of intracellular calcium ion dynamics in human umbilical vein endothelial cells is finally conducted to demonstrate the biological applicability of the proposed microfluidic system.